Sexual Behavior Patterns among Deaf and Hard-of-Hearing Students: A Descriptive-Exploratory Study in West Sumatra, Indonesia - Elsa Efrina; Rahmahtrisilvia Rahmahtrisilvia; Yoga Hadia Sukma; Setia Budi; Endang Rochyadi; Budi Susetyo; Riksma Nurahmi Akhlan; Tati Hernawati; Yoga Budhi Santoso (Universitas Sultan Ageng Tirtayasa, 2026)
Sexual development is a natural aspect of human growth experienced by all students, including Deaf and Hard-of Hearing (DHH) students. However, communication barriers among DHH students may limit their understanding of privacy boundaries and social norms, thereby increasing the risk of inappropriate sexual behaviors. This study aimed to identify the types of observable sexual behaviors among DHH students enrolled in special schools in West Sumatra, Indonesia. A descriptive–exploratory design was employed. The participants consisted of seven teachers from special schools who taught DHH students. Data were collected using an online questionnaire distributed via Google Forms. Quantitative and qualitative analytical techniques were applied to examine the data. The findings indicate that students exhibited various forms of sexual behavior, including non-verbal sexual behaviors, verbal sexual behaviors, self or other endangering sexual behaviors, and extreme behaviors. All participating teachers reported instances of students touching others’ bodies without permission (100%) and pressing or leaning their body against others (75%). These results underscore the importance of targeted sexuality education and communication support for students with DHH within special school settings